Covalent cell surface recruitment of chemotherapeutic polymers enhances selectivity and activity. Issue 12 (18th February 2021) - Tomás, Ruben M. F.; Gibson, Matthew I.
Abstract : Chemotherapeutic polymers are targeted to cells by introduction of unnatural glycans to their glycocalyx, enhancing their cytotoxic effect. Abstract : Synthetic macromolecular chemotherapeutics inspired by host defence peptides can disrupt cell membranes and are emerging as agents for the treatment of cancer and infections. However, their off-target effects remain a major unmet challenge. Here we introduce a covalent recruitment strategy, whereby metabolic oligosaccharide engineering is used to label targeted cells with azido glycans, to subsequently capture chemotherapeutic polymers by a bio-orthogonal click reaction. This results in up to 10-fold reduction in EC50 and widening of the therapeutic window. Cell death is induced by not only membrane leakage, but also by apoptosis due to the conjugated chemotherapeutic being internalised by glycan recycling. Covalent recruitment also lead to increased penetration and significant cell death in a 3-D tumour model in just 3 hours, whereas doxorubicin required 24 hours. This conceptual approach of 'engineering cells to capture polymers' rather than 'engineering polymers to target cells' will bring new opportunities in non-traditional macromolecular therapeutics.